ABaSbQ3 (A = Li, Na; Q = S, Se): diverse arrangement modes of isolated SbQ3 ligands regulating the magnitudes of birefringences. Issue 35 (12th April 2019) - Abudurusuli, Ailijiang; Wu, Kui; Tudi, Abudukadi; Yang, Zhihua; Pan, Shilie
Abstract : The interrelation of arrangement modes of isolated SbQ3 ligands on structures and birefringences has been systematically studied in series of chalcogenides. Abstract : A new series of ABaSbQ3 compounds (A = Li, Na; Q = S, Se) featuring isolated SbQ3 ligands with different arrangement modes was synthesized. The structural transformations (monoclinic to orthorhombic) in the known A–M II –Sb–Q3 system showing an intimate relationship with the differences (Δ d = L IIM–Q − L A–Q ) were systematically investigated for the first time. Remarkably, the diverse arrangement modes of the isolated SbQ3 ligands have also proven effective at regulating the optical anisotropy based on first principles calculation.